Acting on persecutory delusions: the importance of safety seeking. - Freeman, D; Garety, P; Kuipers, E; Fowler, D; Bebbington, P; Dunn, G (2007)
OBJECTIVE: Acting on delusions is a significant clinical issue. The concept of safety behaviours--actions carried out with the intention of reducing perceived threat--provides a new way of understanding acting on delusions. A study was conducted with the aim of examining the prevalence and correlates of safety behaviours related to persecutory delusions. METHOD: One hundred patients with persecutory delusions were assessed for safety behaviours, acting on delusions, anxiety, depression, and psychotic symptoms. Case note data were collected on instances of serious violence or suicide attempts. RESULTS: Ninety-six patients had used safety behaviours in the last month. Greater use of safety behaviours was associated with higher levels of distress. A history of violence or suicide attempts was associated with greater use of safety behaviours. Safety behaviours were significantly associated with acting on delusions, but not with the negative symptoms of psychosis. CONCLUSION: Safety behaviours are a common form of acting on persecutory delusions. These behaviours have the consequence that they are likely to prevent the processing of disconfirmatory evidence and will therefore contribute to delusion persistence.